Comparación del ritmo de crecimiento de las toninas (Tursiops truncatus) pertenecientes a tres localidades distintas - Romero Tenorio, Arturo; Delgado Estrella, Alberto (THERYA, 2015)
Introduction: In order to know the growing rate of the captive bottlenose dolphins (Tursiops truncatus) of Via Delphi, the total length and age from three different geographic zone dolphins, from Quintana Roo and Tabasco in Mexico, and some individuals from Cuba (some dolphins were born in captivity) were recorded. The aim of this study was to establish if there were statistic differences between gender and among dolphins from different localities. Methods: The age of 43 dolphins was determined through the analysis of the growth layers groups (GLGÂ´s), The gender of these dolphins was known, the total length of all of them, and the skull length of 12 toninas. The total sample was composed of 17 males and 26 females. Results: Of these 43 dolphins, 13 were calves between five years to 10 months old. Sexually mature dolphins from Quintana Roo, three males of 18 years old, presented a total length mean of = 253.33 cm + 14 cm S. D. (range 239-267 cm, n = 3). Females older than 10 years old presented a total length mean of = 250.6 cm + 7.5 cm S. D. (range 239-261 cm, n = 8). From de State of Tabasco, males older than nine years old, had a mean total length = 236.13 cm + 5.2 cm S. D. (range 238-240 cm, n = 4). Females were older than eight years old, their mean total length = 239.4 cm + 7.4 cm S. D. (range 227-246 cm, n = 5). About the Cuban dolphins, The sample from the Cuban dolphins was small (seven dolphins), they compared with dolphins of same sex and age of the two localities. Discussion: The values of Lmax of bottlenose dolphins in the Southern of the Gulf of Mexico are similar to the bottlenose dolphins in Texas and Florida, no significant statistical differences were found. Differences in growing rates were not found in the Lmax on adult dolphins between localities nor sexes.